Trends in presentation of bone and soft tissue sarcomas over 25 years: little evidence of earlier diagnosis - Smith, GM (The Royal College of Surgeons of England, 2011)
Earlier diagnosis is a key aim in achieving improved outcomes for patients with cancer. Bone and soft tissue sarcomas represent approximately 1% of all malignant tumours. Delays in diagnosis are frequent both because of their rarity and because the clinical features are easily confused with other conditions. In 2000 advice on earlier diagnosis was widely publicised. This study investigates how two factors that may act as a proxy for delay in diagnosis have varied over a 25-year period and whether there is evidence of improvement. Data on symptom duration and tumour size were collected prospectively on all new sarcoma patients referred to an orthopaedic oncology unit over 25 years. Data were available for 2,568 patients with primary bone sarcomas and 2,366 with soft tissue sarcomas. The mean sarcoma size at diagnosis was 10.7cm and 9.9cm respectively. The size of bone sarcomas had not changed over time but there had been a slight decrease in the size of soft tissue sarcomas (10.3cm before 2000 vs 9.6cm after 2000, p=0.03). The duration of symptoms reported by patients varied widely with a median of 16 weeks for bone sarcomas and 26 weeks for soft tissue sarcomas. The median duration of symptoms for bone sarcomas had actually increased since 2000 (16 weeks before vs 20 weeks after 2000, p<0.01). It remained unchanged for soft tissue sarcomas. These data show there is huge room for improvement in diagnosing bone and soft tissue sarcomas. New strategies are needed urgently.